COMPARATIVE ANALYSIS OF STABILITY INDICATORS OF DENTAL ADHESIVE MATERIALS USED FOR FIXATION OF BRACKETS TO THE TOOTH SURFACE IN ORTHODONTIC TREATMENT (International journal of medical sciences, 2026)
The stability of the adhesive bond between the bracket base and the enamel surface is a fundamental factor determining the success and efficiency of orthodontic treatment. Frequent bracket failure leads to prolonged treatment duration and increased financial costs. This article presents an empirical study conducted at the Department of Orthopedic Stomatology and Orthodontics of Andijan State Medical Institute. The research utilizes the IMRAD structure to evaluate and compare the shear bond strength and adhesive remnant index of three distinct generations of orthodontic adhesive systems. The study involved the mechanical testing of extracted human premolars bonded with conventional light-cure composite, a self-etching primer system, and a resin-modified glass ionomer cement. The results indicate that while conventional light-cure composites offer the highest initial bond strength, self-etching systems provide adequate clinical stability with significantly reduced risk of enamel damage upon removal. The findings suggest that the choice of adhesive material requires a clinical balance between maximum retention and the preservation of the enamel structure.